EFFECT OF PLYOMETRIC EXERCISES ON PHYSICAL FITNESS PREPARATION OF ELITE BALL BADMINTON PLAYER - Sawant, Prashant Chandrakant (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The objective of this research study was to find out the effect of plyometric exercises on physical fitness preparation of elite ball badminton players in the city of Satara. A total of 20 elite male players (aged 17-19) participated in this research study. The samples were selected randomly from a population of collegiate male students and they participated in two tests (the vertical jump and medicine ball throw). After making them homogeneous, the participants samples were randomly divided into two groups, i.e. an experimental group (plyometric exercises) and a control group (only ball badminton exercises). They part of the exercises for 6 weeks with 4 sessions each week and duration of each session for 90 minutes. After implemented of the training plan, both groups conducted of post-test. The ball badminton player’s score were collected in two pre- and post-tests and compared them. The results of the study revealed that 6 weeks of plyometric exercise have a significant effect on the ball badminton players score in two tests (the vertical jump and medicine ball throw) and have caused improvements in the results of these tests. Therefore, it seems that plyometric exercises had an effect on the physical fitness preparation of ball badminton players of experimental group compared to the control group and it’s improve the ball badminton players performance in this field.